Uji Laboratorium Proses Perengkahan Toluen dengan Katalis Reformasi Kukus Ni/a-Al2O3 - Herri Susanto (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Tar formation was one of the major problems in the utilization of syngas produced from gasification of biomass and coal. Toluene was used as a model tar and N2 as carrier gas. Laboratory test was performed using a commercial steam reforming catalyst available in our laboratory. The amount of catalyst was 2,5 g and reaction temperature was varied at 500, 600, 700, and 800oC. The gas flow rate was 0,0077 Nm3/h with a toluene concentration of 51 g/Nm3. Our laboratory test revealed that toluene conversion up to 99,6% might be obtained at the reaction temperature of 8000C and molar steam/toluene ratio of 16. Decreases in toluene conversion were observed when reactions were carried out in a condition of stoichiometric steam to toluene ratio of 7. Kinetics parameters toluene steam reforming on catalyst Ni/a-Al2O3 were obtained experimently by laboratory were Ea of 11,6 kJ/mol and k0 of 272 m3/kgcat.hours. Using these kinetics parameters, toluene might be converted almost completely in a plug flow reactor with a resedence time of 0,35 s, under the following condition: steam to toluene ratio of 16 and temperature above 700oC.